The Dynamics of Phytoplankton Abundance Lake Putus Pangkalan Baru Village Siak Hulu Sub District Kampar District Riau Province - Fahrezzy, Reggi; Dahril, Tengku; Simarmata, Asmika Harnalin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractThe research of phytoplankton abundance dynamics conducted in July-August 2019 at Lake Putus Pangkalan Baru village. A study aims to know the dynamics of phytoplankton abundance by spatial and temporal. There were 3 stations namely station 1 (inlet area), station 2 (in the middle of the lake) and station 3 (in the end of the lake). In each stations, there were 2 sampling point, in the surface and 2 Secchi depth. Sampling was done 4 times, once/week. Water quality parameters measured were temperature, pH, transparency, dissolved oxygen, free carbon dioxide, nitrate, phosphate. Result shown that temperature 29-30 oC, transparency 59-65 cm, pH 5, DO 3.72-5.74 mg/L, CO2 5.99-10.98 mg/L, nitrate 0.020-0.046 mg/L, phosphate 0.028-0.053 mg/L. Phytoplankton abundance at the surface range 124,432-239,976 cell/L, and 2 Secchi depth range 73,326-124,431 cell/L. Temporal and spatial dynamics of phytoplankton abudance was influenced water quality such as transparency, nitrate and phosphate concentration. Keywords: Temporal, Spatial, Water Quality, Depth